2015
DOI: 10.4103/1477-3163.165158
|View full text |Cite
|
Sign up to set email alerts
|

Role of genomics in eliminating health disparities

Abstract: The Texas Center for Health Disparities, a National Institute on Minority Health and Health Disparities Center of Excellence, presents an annual conference to discuss prevention, awareness education, and ongoing research about health disparities both in Texas and among the national population. The 2014 Annual Texas Conference on Health Disparities brought together experts in research, patient care, and community outreach on the “Role of Genomics in Eliminating Health Disparities.” Rapid advances in genomics an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The different SNPs found to be GWAS significant in association with blood folate metabolites may suggest the results of different evolutionary pressure between ethnicities and may lead to population-specific prevention strategies against diseases related to folate metabolism disorders, such as atherosclerosis and CVDs. 58,59 In previous studies, a positive interaction between MTHFR C677T and smoking habits on plasma Hcy was reported. 18,[60][61][62][63] The present study revealed the marginal interaction in the same direction, although it did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The different SNPs found to be GWAS significant in association with blood folate metabolites may suggest the results of different evolutionary pressure between ethnicities and may lead to population-specific prevention strategies against diseases related to folate metabolism disorders, such as atherosclerosis and CVDs. 58,59 In previous studies, a positive interaction between MTHFR C677T and smoking habits on plasma Hcy was reported. 18,[60][61][62][63] The present study revealed the marginal interaction in the same direction, although it did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 91%
“…The different SNPs found to be GWAS significant in association with blood folate metabolites may suggest the results of different evolutionary pressure between ethnicities and may lead to population-specific prevention strategies against diseases related to folate metabolism disorders, such as atherosclerosis and CVDs. 58 , 59 …”
Section: Discussionmentioning
confidence: 99%
“…The minor allele frequencies of the newly detected SNPs for Japanese (those with the top p values in each locus) were 0.2326 in Japanese, 0.0221 in Caucasians, and 0.0974 in Africans for the LRP2 rs3770636 G  allele; 0.4355 in East Asians, 0.0924 in Europeans, and 0.2095 in Africans for the NFATC1 rs74183647 C allele; 0.0288 in East Asians, 0.0010 in Europeans, and 0.0000 in Africans for the rs555786707 A allele on chr 4; and 0.0317 in East Asians, 0.0000 in Europeans, and 0.0000 in Africans for the rs78351985 G allele on chr 4 according to the Single Nucleotide Polymorphism database (dbSNP) (https://www.ncbi.nlm.nih/gov/SNP), all of which are more than 1%, suggesting the substantial involvement of these variants in the regulation of renal functions in Japanese and East Asians. Although worldwide GWAS consortiums of human chronic diseases are flourishing these days, such GWAS of each race/ethnicity may also be considered meaningful, given that the racially/ethnically specific gene-environment interaction could provide more effective ways for disease prevention in each race/ethnicity [7, 40]. The strength of the present study is the large sample size and the densely imputed genetic data, which lead to the discovery of as yet unidentified genetic loci associated with renal functions specifically in Japanese population.…”
Section: Discussionmentioning
confidence: 99%
“…For example, recent GWASs investigating the genetic loci associated with kidney function identified the glucokinase regulator locus on chromosome (chr) 2 as highly significant loci [5, 6]. Additionally, genotype distributions and factors related to lifestyles are known to differ according to races, ethnicity, and nations, which may lead to the existence of diverse population-specific gene-environmental interactions, making the nation-based reports of genetic associations still meaningful for the effective prevention of disease in each population [7]. Recently, a meta-analysis in an East Asian population revealed 17 loci that were newly associated with renal function traits.…”
Section: Introductionmentioning
confidence: 99%
“…Dear editor, Polymorphisms in the vascular endothelial growth factor A (VEGFA) gene and their effect on antihypertensive responses to enalapril were studied by Oliveira-Paula et al, and the results were published recently [1]. With the introduction of modern technologies to determine genetic variations in an individual, the concept of personalized medicine receives increasing acceptance among health care personnel [2].…”
mentioning
confidence: 99%